Effects of N2 pressure on properties of titanium nitride films by filter cathodic vacuum arc for bipolar plates in PEM fuel cells - D. Pejchang (2018)
This research is aimed to synthesize titanium nitride (TiN) thin films on stainless steel 304 using metal vacuum arc surface coating technique. A titanium rod is used as cathode. Plasma is generated by applying the arc pulse voltage of 450 V between the electrodes in N2 atmosphere. The pressure of N2 is varied from 10-5 to 10-3 torr when compare with uncoated-stainless steel 304. The bias voltage for substrate is-1 kV. Then the properties of the films are investigated. Firstly, microstructures of TiN thin films are indentified by X-ray diffraction method (XRD) and the crosssection scanning electron microscopy (SEM) is used to measure the thickness. Secondly, the corrosion resistance is examined by electrochemical test in 1 M H2SO4 solution at 25°C. The electrical resistivity is analyzed by interfacial contact resistance measurements. © (2012) Trans Tech Publications, Switzerland.